Human Rights-Based Approach to Development in the Border Areas (Besitang sub-District, North Sumatra) - Prayetno Prayetno; Majda El Muhtaj; Fazli Rachman; Reh Bungana Beru Perangin-angin (LPPM Universitas PGRI Sumatera Barat, 2025)
Strengthening sub-district government capacity after the emergence of the regional autonomy policy in Reform era of Indonesia is really mandated to incorporating a human rights-based approach to development (HRBA). As a conceptual framework, HRBA seeks to address the root of the problem and touch the interests of the most vulnerable groups from human rights violations due to isolated development of border areas and marginalization of human rights protection. HRBA has become an important and interesting issue in the formulation of sustainable development that are able to empower and even improve the welfare of society. This article examines the government's capacity of the Besitang sub-District in planning and driving action HRBA into development practices in their regions. The article resulted from qualitative descriptive research. Data were collected by using focused group discussions, field studies, and literature review, then analysed through an interactive analysis. Finally, this article concludes that improving the performance of apparatus and good mechanisms for institutional assistance at the village level, including community leaders and disadvantages of community participation, is a significant effort to accelerate the realization of HRBA in Besitang sub-District.